Unilateral diaphragmatic palsy and pleuropericarditis in a patient with granulomatosis with polyangiitis: a case report - Ujjwol Prasad Risal; Raju Prasad Pangeni; Rakshya Pandey; Pradeep Raj Regmi; Aditi Karki; Avish Shah (Journal of Medical Case Reports, 2023)
Abstract Background Granulomatosis with polyangiitis (GPA) is a rare small vessel vasculitis predominantly affecting upper and lower respiratory tract and kidneys. Unilateral diaphragmatic palsy could be a rare manifestation of GPA. Here we report a case of GPA in a 45-year-old male with unilateral diaphragmatic palsy with pleuropericarditis. Case presentation We report a case of a 45-year-old Khas male who presented with acute onset chest pain and shortness of breath who had elevated right hemidiaphragm, bilateral pleural effusion and pericardial effusion who was later diagnosed as GPA. Conclusions GPA should be suspected in all patients with diaphragmatic palsy and pleuropericarditis with appropriate clinical and laboratory picture.